The role of central reading centers - current practices and future directions - Tan, Colin; Sadda, Srinivas (Indian journal of ophthalmology, 2015)
Central reading centers (CRCs) have several crucial roles in the conduct of clinical trials, providing key input during the study design, preparation of the operations manual, as well as site and photographer certification. They provide objective, standardized grading of images from study subjects, which determines study eligibility, and also evaluate lesion features at subsequent study visits. CRCs need to adhere strictly to Good Clinical Practice (GCP) guidelines, as well as the established standard operating procedures in order to ensure that images are graded properly. The role of CRCs will continue to evolve, and include the use of web-based image transmission and grading platforms.